Control of a pointer located on a vibrating system - Casciati, F.; Faraveli, L.; Anh, Nguyen Dong (Vietnam Journal of Mechanics, 2001)
In this paper, the problem of controlling a bar supporting, at one end a pointer and hinged, at the other end, to a structural system vibrating under any extern excitation is investigated. The problem is to maintain the pointer toward the target with a prescribed tolerance. Emphasis is put on the uncertainty, which characterizes the problem and a simple fuzzy controller approach is discussed. Some numerical simulations are presented